Polysaccharide‐Induced Immunoregulation, Signaling Pathways, and Stress Mitigation in Aquaculture Animals: A Review - Md. Akibul Hasan Bakky; Peijun Yi; Ngoc Tuan Tran; Qian Sun; Ming Zhang; Yueling Zhang; Shengkang Li (Reviews in Aquaculture, 2025)
Aquaculture, encompassing the cultivation of diverse saltwater and freshwater fish and shellfish species, is rapidly expanding, driven by the pressing need for sustainable food production. However, intensified farming practices often lead to significant economic losses due to fish mortality from infectious diseases and stress‐related conditions. Consequently, enhancing the immune responses of farmed species has become vital for sustainable management. This has encouraged a growing interest in natural and eco‐friendly bioactive compounds as alternatives to synthetic chemicals for disease prevention. Among these, polysaccharides from various natural sources have emerged as promising candidates, administered through dietary inclusion, intraperitoneal injection, or immersion. As prebiotics, these polysaccharides enhance the immunity and overall health of aquaculture species by modulating both innate and adaptive immune responses, including lysozyme activity, phagocytosis, and cytokine production. This review critically examines the latest advances in polysaccharide‐induced immunoregulation, highlighting their influence on key signaling pathways, which play pivotal roles in immune modulation. Additionally, the potential of polysaccharides to mitigate stress caused by environmental factors is discussed, demonstrating their ability to enhance growth performance and disease resistance. The collective findings underscore the value of polysaccharides as sustainable alternatives to antibiotics, aligning with the increasing consumer demand for antibiotic‐free aquaculture products and supporting the advancement of global aquaculture sustainability.